Estetika Penggunaan Majas dalam Lirik Lagu Nadin Amizah: Kajian Stilistika - Panuntun, Gadi Agung; suhartatik, suhartatik; Hodairiyah, Hodairiyah (STKIP PGRI SUMENEP, 2024)
This research aims to describe the use of figures of speech in Nadin Amizah's song lyrics and how this contributes to the aesthetic value of the song lyrics. This research uses a qualitative descriptive approach. The results of this research found that in the collection of Nadin Amizah's song lyrics, 10 types of language styles and 2 types of aesthetic representation were found, namely linguistic and mental. This finding confirms that Nadin Amizah's collection of song lyrics uses a variety of language styles to support the aesthetic value in them.Keywords: Stylistics, Aesthetics, Figure of Speech, Song Lyrics, Nadin Amizah